Fc-Galactosylation of Human Immunoglobulin Gamma Isotypes Improves C1q Binding and Enhances Complement-Dependent Cytotoxicity - Peschke, Benjamin; Keller, Christian W.; Weber, Patrick; Quast, Isaak; Lünemann, Jan D. (Frontiers in Immunology, 2017)
Binding of the complement component C1q to the CH2 domain of antigen-bound IgG activates the classical complement pathway and depends on its close proximity to Fc fragments of neighboring antibodies. IgG subclasses contain a highly conserved asparagine 297 (N)-linked biantennary glycan within their CH2 domains which core structure can be extended with terminal galactose and sialic acid residues. To investigate whether Fc-glycosylation regulates effector functions of human IgG subclasses, we cloned the antigen binding region of the CD20-specific monoclonal antibody rituximab into IgG isotype expression vectors. We found that Fc-galactosylation enhances the efficacy of CD20-targeting complement-fixing antibodies for C1q binding and complement-mediated tumor cell lysis. Increased efficacies were restricted to IgG1 and IgG3 subclasses indicating that Fc-galactosylation of IgG2 and IgG4 isotypes alone is not sufficient to activate the classical complement pathway. Addition of terminal galactose to the N-glycan specifically improved binding of C1q without changing antigen- and FcγRIIIa-binding affinities of IgG isotypes. These data indicate that Fc galactosylation can be harnessed to enhance the complement-activating properties of C1q-fixing IgG1 and IgG3 antibodies.